2015
DOI: 10.1155/2015/848710
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of MicroRNAs by Phytochemicals in Cancer: Underlying Mechanisms and Translational Significance

Abstract: MicroRNAs (miRNAs) are small, endogenous noncoding RNAs that regulate a variety of biological processes such as differentiation, development, and survival. Recent studies suggest that miRNAs are dysregulated in cancer and play critical roles in cancer initiation, progression, and chemoresistance. Therefore, exploitation of miRNAs as targets for cancer prevention and therapy could be a promising approach. Extensive evidence suggests that many naturally occurring phytochemicals regulate the expression of numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 109 publications
(108 reference statements)
0
46
0
1
Order By: Relevance
“…future science group www.futuremedicine.com Natural products are important and valuable resources for drug development, with a long history of use in treating human ailments, particularly for almost all kinds of cancer [21]. Early drug discovery was based on screening of a large number of natural and synthetic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…future science group www.futuremedicine.com Natural products are important and valuable resources for drug development, with a long history of use in treating human ailments, particularly for almost all kinds of cancer [21]. Early drug discovery was based on screening of a large number of natural and synthetic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that p300/CBP activity can be targeted by curcumin in cervical and other cancers [46,47] . There are also lines of evidence showing that curcumin prevents histone hyperacetylation and alters miRNA expression in cancers other than cervical cancer [48,49] . Similarly, genistein is known to affect histone acetylation or DNA methylation [50,51] Alcohol consumption and smoking are important risk factors for cervical carcinogenesis.…”
Section: Nutrition Diet Epigenetics and Cervical Cancermentioning
confidence: 99%
“…Sometimes, the reason of the deregulation of these microRNAs is known e over 50% of microRNAs are situated on fragile genomic regions in cancer [10,11]. Sometimes, their functions were even decrypted, leading to the concept of oncomiRs and microRNA tumor suppressors [3,5,11].…”
mentioning
confidence: 99%
“…Concretely, there are only 2 microRNA-related drugs in Phase 1 and Phase 2 of clinical trials respectively: Mirna Therapeutics started in 2013 to test the microRNA mimic of miR-34a, a tumor suppressor regulating at least 24 oncogenes, in patients suffering from primary liver cancer and liver metastases [10,15]. Good results were obtained in the meantime by Miravirsen, which antagonizes miR-122, essential for hepatitis C virus (HCV) replication [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation